Effect of Varicocele on Spermatogenesis (Bangladesh Journal of Urology, 2020)
Objective: To evaluate the effects of varicocele on spermatogenesisand determine its association with oligospermia or azoospermia.Methods: This observational study was conducted from January 2010 to December 2011, in the Department of urology & surgery of DMCH on 100 adolescents & adults with unilateral or bilateral varicocele of grade I to III. Patients with cryptorchidism, testicular trauma, surgery of the urogenital tract and secondary varicoceles were excluded. Detailed history was taken and physical examination was done to diagnose varicocele with its grading and was reconfirmed by ultrasonogram with Color Doppler. Semen was collected accordingly and was examined within 90 minutes of collection. Chi-square (c2) Test and unpaired t- Test was used for qualitative for quantitative variables respectively andp 10 yrs.) patients were 2.7 times more likely to be oligospermic or azoospermic than those with shorter duration (p-0.020). Over 80% of the oligo or azoospermic patients belonged to grade III varicocele compared to 53.1% with normal sperm count (p-0.006).Conclusion: Men with varicocele tend to be infertile and there is an increasing chance of being infertile with longer duration and higher grade (grade-III) of the disease. The age of the patients or side of varicocele were not found to be associated with oligo or azoospermia.Bangladesh Journal of Urology, Vol. 20, No. 1, January 2017 p.3-7